Serial changes in plasma brain natriuretic peptide in patiens treated with conventional stenting or direct stenting: a comparative study - Khan, Saidur Rahman (My University, 2003)
unknown
Keywords: Hastalıklar; Kalp damar sistemi hastalıkları; Kalp hastalıkları; Kardiyoloji; Teknoloji (Uygulamalı bilimler); Tıp bilimleri